Analisis Pengembangan Kawasan Berbasis Komoditas Palawija pada Kota Jayapura - Anggraeni Wahyu Murti; Julius Ary Mollet; Halomoan Hutajulu (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The city of Jayapura has potential in the agricultural sector where there are people who take advantage of the potential in the field of secondary crops. Agricultural commodity crops in Jayapura City are in the form of food crops, namely paddy rice, corn, beans, and tubers which are cultivated in this region. Palawija commodities developed in this region have potential and can be sold to other regions but have not had a significant impact on regional income and the community. The analytical method used is Location Quotient and Shift Share analysis which are combined to find out the leading commodities in the Jayapura City area and then SWOT analysis, to determine directions and strategies for regional development based on grain commodities. The results of the analysis show that the leading commodity crops in Jayapura City are Sweet Potatoes with a local economy-based commodity development strategy with efforts to increase the production of secondary crops, especially sweet potato commodities, increase product processing innovation, and farmer group expertise